The European Commission – Appointment, Preferences and Institutional Relations - Stefan Napel; Mika Widgrén (Aboa Centre for Economics (ACE), 2006)
The paper analyzes the appointment of the European Commission as a strategic game between members of the European Parliament and the Council. The focal equilibrium results in Commissioners that duplicate policy preferences of national Council representatives. Different internal decision rules still prevent the Commission from being a Council clone in aggregate. Rather, it is predicted a priori that Commission policies are on average more in accord with the aggregate position of the Parliament. Empirical analysis suggests that the Council is, in fact, significantly more conservative than Parliament and Commission; the latter two are significantly closer to each other than Council and Commission.
Keywords: C70; D71; H77; 330; European Commission; investiture procedure; voting rules; Council of Ministers; European Parliament